Contrasting trends in gender and childcare in Argentina: Family policies between LGBT rights and maternalism. (July 2018) - Faur, Eleonor
This article analyses the stark contrast between the revolutionary shift in LGBT rights and the maternalistic shadow still cast over childcare-related family policies in Argentina. It analyses family law and recent developments in the recognition of women and the LGBT population as equal rights holders in the realm of the family. Then it examines family policies aimed at working parents with childcare responsibilities, exploring whether or not the enactment of the Egalitarian Marriage Act shifted the consideration of working mothers and fathers' rights and obligations regarding childcare. Finally, it discusses the challenges in implementing policies that can disentangle the gender and social inequalities embedded in them. The author argues that different logics are found in different family regulations. Family laws introduced gender neutral language and equal parental responsibilities, but family policies still distinguish rights and responsibilities according to gender even after the postpartum period. These not only misrecognize the LGBT population, but they also reaffirm maternalistic assumptions that do not reflect the new family dynamic and recent legal advances. In addition, in the most unequal region of the world, reinforce a system of socioeconomic and gender inequalities.